2017
DOI: 10.1149/2.0551704jes
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanistic Study of Dissolution of Pt–Fe Binary Alloys in 0.5 M H2SO4Solution by Channel Flow Triple Electrode

Abstract: A channel flow triple electrode (CFTE) was applied for the in situ detection of Fe ions (Fe(II) and Fe(III)) and Pt ions (Pt(II) and Pt(IV)) dissolved from Pt-50at%Fe (Pt-50Fe) and Pt-25at%Fe (Pt-25Fe), under potential cycling in 0.5 M H 2 SO 4 at 298 K. These ions, dissolved from a Pt-Fe alloy working electrode set upstream in a channel, were simultaneously detected on two Au collector electrodes placed downstream by reducing or oxidizing their dissolved ions. When Pt-50Fe was potential-cycled between 0.05 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…The dissolution of alloying elements is an additional concern about Pt alloy catalysts [36,37]. Some studies on the dissolution of alloying elements from Pt alloy electrodes have indicated that the dissolution of Pt skin layers triggers the dissolution of the alloying elements [38][39][40]; the corrosion resistance of the Pt skin layer formed on Pt-Co contributes enormously to the durability of Pt-Co alloy catalysts under the PEFC-operating condition. However, the dissolution behavior of the Pt skin layer in the simulated PEFCoperating conditions remains unclear because the corrosion resistance of the Pt skin layer cannot be evaluated by durability tests using Pt-Co nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…The dissolution of alloying elements is an additional concern about Pt alloy catalysts [36,37]. Some studies on the dissolution of alloying elements from Pt alloy electrodes have indicated that the dissolution of Pt skin layers triggers the dissolution of the alloying elements [38][39][40]; the corrosion resistance of the Pt skin layer formed on Pt-Co contributes enormously to the durability of Pt-Co alloy catalysts under the PEFC-operating condition. However, the dissolution behavior of the Pt skin layer in the simulated PEFCoperating conditions remains unclear because the corrosion resistance of the Pt skin layer cannot be evaluated by durability tests using Pt-Co nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, it was revealed that Pt surface diffusion and dissolution accelerated Fe dissolution from Pt-50Fe during potential cycling using CFME. 26 The dissolution mechanism of Pt-50Cu was probably similar to that of Pt-50Fe, and that Cu dissolution was not suppressed by the Ptenriched layer in the later stage of potential cycling.…”
Section: Resultsmentioning
confidence: 93%
“…Furthermore, the current of Pt-50Cu was smaller than that of Pt-50Fe and was somewhat similar to that of Pt-25Fe. 26 In other words, the Pt-Cu alloys exhibited higher durability compared to Pt-Fe alloys when the alloy composition was the same. These results are in line with those in our previous work.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, in order to clarify the dissolution behavior of PtM alloys in detail, a channel-flow multi-electrode (CFME) has been developed. 18,19) CFME can be used to provide information on the potential ranges and valences of Pt and Fe dissolved from PtFe alloys. Moreover, many researchers have attempted to develop online ICP-MS measurement systems with high detection sensitivities for dissolved ions and almost no limitation on the elements that can be analyzed.…”
Section: Introductionmentioning
confidence: 99%